Metode Amtsilati Dalam Mempercepat Kemampuan Baca Kitab Kuning (Studi Kasus di Pondok Pesantren Nurul Ulum Malang) - Muhammad Arif Nasruddin; Much Nasikhon Amin (Cordova Journal language and culture studies, 2022)
Learning Arabic with the aim of being able to read and understand Arabic literacy seems to take a long time, these conditions encourage Arabic language experts to mix and find methods that can accelerate the ability of Arabic learners to read and understand bare Arabic literacy. Among the existing methods, the Amtsilati Method is one of the most effective.This study aims to determine how the implementation of the amtsilati method in accelerating the ability to read the yellow book of students at the Nurul Ulum Islamic Boarding School Malang, the ability to read the yellow book and the supporting and inhibiting factors. The type of research used is descriptive qualitative research method with the type of field research or field research. The data analysis technique used descriptive qualitative with the following steps: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the implementation of the amtsilati method in accelerating the ability to read the yellow book is going well and plays an important role in supporting the success of the santri learning method which is marked by enthusiasm and the success of reading the yellow book within 6 months.